TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR INDONESIA - Titis Nistia Sari; Dabella Yunia (Universitas Bina Bangsa, 2021)
A complicated tax problem in Indonesia is tax avoidance. Tax avoidance is a legal action that is detrimental to the state. This research aims to determine whether tax avoidance affects leverage, firm size and return on assets. This study was tested using multiple linear regression with the dependent variable tax avoidance and independent variables in the form of leverage, firm size, and return on assets. The population in this research is companies that listed in Indonesian Stck Exchanged (www.idx.co.id) and sample in this study amounted to 50 (fifty) manufacturing companies. The selection of the research sample was done by random sampling. Multiple regression testing uses SPSS 25 software. The results show that leverage has a positive effect on tax avoidance, while firm size and return on assets have no effect on tax avoidance. Companies with high debt levels tend to do tax avoidance. On the other hand, companies of any size and any return on assets can carry out tax avoidance